(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Many natural streams, which are locally known as ’Jans’, serve Jorhat area. The crucial thing to note is that the bed level is far higher than the bed level of the other natural cum man-made streams of the main river of this town of Bhogdoi. Draining storm water directly into the Bhogdoi River is challenging. Therefore, where sufficient gradient is available, it is suggested to drain out the storm water to the jans. The flood water is pumped away mostly through overland flow across the fields to rivulets in regions beyond the urban border. The surface drains and the natural waterways are transported through power and sewage. The rapid industrialization and increase in urban settlements, the indiscriminate disposal of waste and the exploitation of these natural channels pose significant risks to the life of natural waterways, resulting throughout water logging in the rainy season in certain regions. Many parts of the city experience water logging throughout the rainy season due to human intervention. Over the last few years, this issue has become more complex, as this waste disposal is causing tremendous siltation on the Bhogdoi Channel. The river Bhogdoi receives more flood waves in Jorhat than any other river on the south side of Brahmaputra. Comparison to the other rivers on the south bank in upper Assam, the flood level of the river is very lower.